Influence of Physical-Metallurgical Factors on Resistance of API Carbon Steels to Sulphide Stress Cracking - Jonsta, Petr; Jonsta, Zdenek; Vlckova, Irena; Sojka, Jaroslav (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with the influence of physical-metallurgical factors on resistance of the X52 and X70 steels in accordance with API 5L to sulphide stress cracking. The resistance against this kind of damage is relatively clearly claimed by usually used approach in this field by the tensile strength of steel, its hardness level, respectively. However, the experimental results had shown that the microstructural parameters are also the significant factors, which affect the resistance of steels to sulphide stress cracking. It was found that the quenching and tempering can significantly increase the resistance to sulphide cracking as in the case of hydrogen induced cracking. It would be appropriate to re-evaluate the material selection process that recommends to use the steels not exceeding approved strength limit in a case of the sulfane environments where the risk of the sulphide stress cracking exists.